Antidiabetic Properties of Uncaria sclerophylla Roxb: In Vitro, Metabolite Profiling, and Molecular Docking - Nita Triadisti; Muhammad Hanafi; Najihah Mohd Hashim; Berna Elya (Emerging Science Journal, 2026)
Uncaria sclerophylla Roxb is a traditional medicinal plant used to treat diabetes mellitus in Kalimantan, Indonesia, and the antidiabetic properties of its stem bark have not been previously investigated. This research will focus on investigating the potential of U. sclerophylla stem bark as an antidiabetic with the mechanism of inhibiting dipeptidyl peptidase-4, α-glucosidase, and antioxidants from extracts to chromatographic fractions, including the exploration of the major compounds contained in the most active chromatographic fraction. Extraction using a four-grade maceration technique, bioassays were carried out using spectrophotometric methods, fractionation using gradient column chromatography, and compound profiling using UHPLC-Q-ToF-MS/MS. The profiled compounds were predicted for their bioactivity in silico. The stem bark of U. sclerophylla demonstrated antidiabetic potential, and the methanol extract showed superior antidiabetic potential compared with the other extracts. From the extract, the most active chromatographic fraction, FUS2, was successfully obtained, which had the best activity with DPP-4 inhibition IC50 of 83.07 ± 6.3393 µg/mL, α-glucosidase inhibition IC50 of 58.06 ± 1.6226 µg/mL, and antioxidant IC50 of 8.47 ± 0.0443 (DPPH method) and 8.47 ± 0.0234 µg/mL (FRAP method). Compound profiling of FUS2 and in silico bioassays revealed potential antidiabetic compounds, including rhynchophyllic acid, arecatannin A2, silydianin, and procyanidin A2.